Nursery plants recommendation system using collaborative filtering technique / Madihah Hannani Hashim, Shafiqah Alya Khedzer and Hajar Izzati Mohd Ghazalli - Hashim, Madihah Hannani; Khedzer, Shafiqah Alya; Mohd Ghazalli, Hajar Izzati (Faculty of Computer and Mathematical Sciences, 2022)
During the pandemic, most of the shops cannot be opened. So, it is difficult for the customer to meet and ask the expert such as the nursery keeper about the plants. Other than that, the customer usually takes more time to gather the information about the plants that they want to buy. The item-based collaborative filtering technique that is adapted in the system gives the recommendation to the customer based on the plants that they have bought. It will calculate the similarity between the items and calculate the rate that the customer gives when purchasing the plants. The methodology used is Modified Waterfall Model. The result shows that the system recommends items (plants) to the user, which is it based on the previous rating from other users. It can be concluded that that the item-based collaborative filtering technique gives is the plants recommendation to the customer and Modified Waterfall Model is an efficient design to develop the system.